The better tree fort - Kerrin, Jessica Scott; Leng, Qin (Toronto : Groundwood Books/House of Anansi Press, 2018)
When his dad builds him a tree fort, Russell thinks it is perfect--right up until he notices another tree fort going up three houses over.--from Publishers description.
A Junior Library Guild selection, April 2018.
Keywords: Tree houses -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Tree houses -- Fiction; Fathers and sons -- Fiction; JUVENILE FICTION -- Boys & Men; JUVENILE FICTION -- Family -- Parents; JUVENILE FICTION -- Social Themes -- Self-Esteem & Self-Reliance.; Tree houses; Fathers and sons; Contentment -- Fiction; Father-son relationship -- Fiction; Neighbors -- Fiction; Tree houses -- Fiction; Fiction; Juvenile works; Picture books